Analiza inwestycji ekologicznych w województwie opolskim w ujęciu rodzajowym - analiza retrospektywna - Jakubczyk, Zbigniew (An analysis of different types of ecological investments in the Opole Region - a retrospect, 2007)
In the article, ecological investments in the Opole region are analyzed. First, the investments in the whole of Poland are analyzed from a macroeconomic point of view. In the rest of the article the analysis concentrates on the Opole region. The time interval 1994-2003 is divided into three periods. The first period (1993-1997) is characterized by a dynamie inerease in investment outlays on environmental protection. In the second period (1998-2001) there was a significant decline in investments, which is related to the generał crisis in public finance in Poland. In the third period, an inerease in investment outlays can be observed, although this inerease is smaller than in the First period. During the whole period, the structure of investment changed. Most clearly is the decline in investment in air protection while investment outlays on water protection inereased at the same time.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 315-322